Study on the Impacts of Agricultural Digitalization on Food Supply Chain Resilience from the Perspective of Food Security - Huiyu LIU; Lizhi XU (Guangdong nongye kexue)
【Objective】In the context of increasing global and regional external shocks threatening food security, enhancing the resilience of food supply chains is of paramount importance. The study aims to explore whether agricultural digitalization can significantly enhance the resilience of food supply chains, and it delves into the underlying mechanisms to provide decision-making support for governments and agricultural stakeholders.【Method】Based on the panel data from 31 provinces in China between 2013 and 2022, the baseline regression method and panel threshold model were used to examine the impacts of agricultural digitalization on the resilience of food supply chains. Robustness checks were performed by substituting explained variables, excluding municipal samples, and using instrumental variables for endogeneity test. In addition, regional heterogeneity was analyzed to investigate differences among regions, and the threshold effect of agricultural subsidies was tested.【Result】Agricultural digitalization has significantly enhanced the resilience of the food supply chain, with transaction digitalization playing a pivotal role in this improvement. Specifically, the coefficient for the improvement of agricultural digitalization on food supply chain resilience is 0.108 (P < 0.01), which is further validated through robustness checks. Regional heterogeneity analysis reveals that agricultural digitalization has the most significant positive effect on food supply chain resilience in the western region, followed by. the central region, while the eastern region shows an insignificant. Moreover, agricultural fiscal subsidies exhibit a threshold effect, where the positive impact of digitalization on resilience increases substantially (P < 0.01) once subsidy levels exceed the specific threshold value (0.8996).【Conclusion】Agricultural digitalization is an important pathway for enhancing the resilience of the food supply chain, particularly through transaction digitalization, which accelerates information flow and increases market transparency. Given regional disparities, It is essential to leverage the threshold effect by adjusting agricultural fiscal subsidy policies and promoting the development of regional digital trading platforms, thereby enhancing the stability and flexibility of food supply chains and ensuring food security comprehensively.